APRESENTAÇÃO DE CONCEITOS DE MÁQUINAS DE TURING EM UM AMBIENTE DE REALIDADE VIRTUAL IMERSIVO - XAVIER, Thiago Augusto Alencar; LIMA, André Chastel; MÁRQUEZ, Mercedes Rocío Gonzales; MULLER, Raquel Marcia; FILHO, Rubens Barbosa (ANAIS DO ENIC, 2026)
.